Energy-GDP Nexus for Oil-Exporting Country: The Case of Bahrain - Abou Elseoud, Mohamed Sayed; Kreishan, Fuad M. (International Journal of Energy Economics and Policy, 2020)
The main objective of this paper is to investigate the relationships between electricity consumption and economic growth in Bahrain between 1980 and 2019, utilizing the Autoregressive Distributed Lag (ARDL) model. Estimates revealed the existence of a long run equilibrium relationship between the electricity consumptions per capita and GDP per capita. The Pairwise Granger Causality Test results indicated a unidirectional causality running from electricity consumption to economic growth. The estimation results provide a strong support for the Growth hypothesis in Bahrain, suggesting that Bahrain economy is Energy-dependent. Therefore, it should be taken into consideration that energy consumption has effect on economic growth rates by policy makers. Keywords: Economic growth, Energy, ARDL, Granger Causality, Bahrain JEL Classifications: O13; Q43; C33 DOI: https://doi.org/10.32479/ijeep.9883